New approach for modeling randomly distributed CNT reinforced polymer nanocomposite with van der Waals interactions - Caliskan, Umut; Gulsen, Hilal; Apalak, Mustafa Kemal (Mechanics of advanced materials and structures, 2024)
This paper presents a new approach for the prediction of the stiffness of randomly distributed CNT/polymer nanocomposites using molecular and micromechanics methods with the van der Waals (VdW) interactions. A multi-scale modeling technique was designed for CNT nanoparticles randomly embedded in the polymer using an AMBER force field. This multi-scale model constitutes a representative volume element. The representative volume element consists of polymer, CNT nanoparticle, CNT-polymer interfacial region and Van der Waals bonds. A programming code was developed that randomly distributes nanoparticles according to the desired volume fraction. Python scripting language was used for the modeling technique performed in a finite element environment. By modeling the interfacial regions around randomly distributed CNTs, van der Waals bonds are modeled stochastically. In this study, the subject of interest is the number of CNTs positioned in the RVE according to the volume fraction. These numbers were determined at the level allowed by finite element equations and computational solvers and their effects were investigated by calculated stiffness behavior.